Peran Data Flow Diagram dalam Mengidentifikasi Kebutuhan Fungsional Sistem Informasi - Diki Wahyu Nugraha; Arief Hertadi Rustam; M. Thamrin Basri (Jurnal Sistem Informasi, Sains Data, dan Informatika, 2026)
Identifying functional requirements is a crucial stage in information system development because it determines the suitability of the system to user needs. Errors at this stage can cause the entire system to fail. This study aims to analyze the role of Data Flow Diagrams (DFDs) in identifying the functional requirements of information systems in a systematic and structured manner. The research method used is a descriptive qualitative method with a literature study and system model analysis approach. Data was collected through a review of system design documents and process modeling using DFD, including context diagrams, level 0 DFD, and advanced level DFD. The results show that DFDs are capable of clearly depicting data flows, processes, and interactions between entities, thereby facilitating system analysts in identifying the main functions of the system and user requirements. Thus, the use of DFDs plays an important role in minimizing errors in requirements analysis and improving the quality of information system design.